Low-volatility environment-friendly softening oil as well as preparation method and application thereof
By blending FCC oil slurry and reducing line oil, and loading nano zero-valent metals on coffee ground biochar, the problem of low aroma and high volatility of polymer-modified asphalt waterproof roll softened oil is solved, significantly improving the material's anti-aging performance and joint peel strength.
Patent Information
- Application Number
- CN202411858250.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing polymer-modified asphalt waterproof rolls use high saturation content and low aroma content, resulting in low seam peel strength and poor anti-aging performance. The volatile components in the FCC oil slurry will release harmful flue gas, affecting health and material aging.
The aroma-rich FCC oil slurry is blended with the saturated reduced-line oil, and the coffee ground biochar is used as the smoke inhibitor matrix to load the coffee ground biochar with nano zero-valent metal to improve the adsorption and degradation ability of volatile flue gas.
It improves the anti-aging performance of polymer-modified asphalt waterproof coils, reduces the volatility of softened oil, and the emission of harmful flue gases, and enhances the material's joint peel strength and high and low temperature performance.
Smart Images

Figure BDA0005192478180000071 
Figure BDA0005192478180000091 
Figure BDA0005192478180000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a low-volatile environmentally friendly softening oil and a preparation method and application thereof. Background Art
[0002] Polymer modified asphalt waterproofing membranes have been widely used in building waterproofing projects due to their excellent high and low temperature performance and easy construction characteristics. The main raw materials of polymer modified asphalt waterproofing membranes include asphalt, polymer modifiers (such as SBS, rubber powder, etc.), softening oil, filler and polyester base. The role of softening oil is to improve the low-temperature flexibility of waterproofing membranes. Commonly used softening oils include reduced line oil, cyclohexane oil and recycled waste oil, but these softening oils have high saturated content and relatively low aromatic content, resulting in low joint peel strength and poor anti-aging performance of waterproofing membranes.
[0003] The heavy oil produced in the process of petroleum refining can be converted into light oil such as gasoline, diesel and liquefied gas through catalytic cracking (FCC). FCC slurry oil is part of the material separated by the catalytic cracking unit to improve the yield and processing capacity of light oil. The main components are aromatics, saturated components and colloids, among which the content of aromatics exceeds 50%. Since FCC slurry oil contains a large amount of aromatics, it can be blended with the sideline oil (cut oil) of crude oil vacuum distillation with a high content of saturated components to adjust the ratio of saturated components and aromatic components in the cut oil, thereby providing high-quality softening oil for polymer-modified asphalt waterproofing membranes. However, FCC slurry oil contains a large amount of volatile components, which will release harmful fumes during the preparation process of waterproofing membranes, which not only has an adverse effect on human health, but also accelerates the aging of waterproofing membranes, limiting its application. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a low-volatile environmentally friendly softening oil and a preparation method and application thereof in view of the shortcomings of the prior art. FCC oil slurry rich in aromatic components and line-cutting oil rich in saturated components are blended, and coffee grounds biochar is used as a smoke suppressant matrix. Nano-zero-valent metals are loaded on the coffee grounds biochar using a green and environmentally friendly process to improve the adsorption and degradation of volatile smoke from FCC oil slurry and line-cutting oil, and improve the anti-aging performance of polymer-modified asphalt waterproofing membranes.
[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a low-volatile environmentally friendly softening oil, comprising the following raw materials in parts by weight: 100 parts of FCC oil slurry, 50-150 parts of reduced line oil, and 1-5 parts of nano zero-valent metal loaded coffee grounds biochar.
[0006] Preferably, the low-volatile environmentally friendly softening oil comprises the following raw materials in parts by weight: 100 parts of FCC oil slurry, 80-120 parts of reduced line oil, and 2-3 parts of nano zero-valent metal loaded coffee grounds biochar.
[0007] In the above scheme, the FCC slurry has a freezing point of 15-25°C and a density of 1.03-1.07 g / cm 3 The saturated content is 20-30%, and the aromatic content is 50-65%.
[0008] In the above scheme, the reduced line oil is reduced line oil or reduced line oil, with a solidification point of -5 to -20 ° C and a density of 0.8 to 1.0 g / cm 3 The saturated content is 50-65%, and the aromatic content is 20-40%.
[0009] In the above scheme, the method for preparing the nano zero-valent metal loaded coffee grounds biochar comprises the steps of:
[0010] 1) using an ethanol solution as an extractant to perform Soxhlet extraction on coffee grounds to obtain an extract and extraction grounds;
[0011] 2) After drying the extraction residue, heating and carbonizing it in a sealed and oxygen-free environment to obtain coffee residue biochar;
[0012] 3) After the metal salt is dissolved in water, the pH is adjusted with a sodium hydroxide solution, and then the coffee grounds biochar and the extract are added and mixed evenly, and then polyethylene glycol is added, and the temperature is raised and stirred for reaction. After the reaction is completed, the solid and liquid are separated, and the solid is dried to obtain nano zero-valent metal-loaded coffee grounds biochar.
[0013] Furthermore, the volume fraction of the ethanol solution is 60-80%.
[0014] Furthermore, the volume ratio of the mass of the coffee grounds to the ethanol solution is (5-10) g:200 mL.
[0015] Furthermore, the particle size of the coffee grounds is 100-500 meshes.
[0016] Furthermore, the extraction temperature of the Soxhlet extraction is 95-105° C., and the extraction time is 2-4 hours.
[0017] Furthermore, the extraction residue is vacuum dried at a temperature of 70 to 90° C. for a drying time of 6 to 12 hours.
[0018] Furthermore, the carbonization heating rate is 10-15°C / min, the carbonization temperature is 400-600°C, and the carbonization time is 2-4h.
[0019] Furthermore, the particle size of the coffee grounds biochar is 100 to 500 meshes.
[0020] Furthermore, the metal salt is one of an iron salt, a copper salt and a zinc salt.
[0021] Preferably, the metal salt is one of FeSO4·7H2O, CuSO4·6H2O, and ZnSO4·7H2O.
[0022] Furthermore, the volume ratio of the amount of the metal salt to water is (0.01-0.05) mol:100 mL.
[0023] Furthermore, the concentration of the sodium hydroxide solution is 0.1-0.2 mol / L, the pH is adjusted to 5-6, and ultrasonic treatment is performed for 5-15 minutes after adjustment.
[0024] Furthermore, the mass ratio of the molar amount of the metal salt to the coffee grounds is (0.02-0.06) mol:10g.
[0025] Furthermore, the mass ratio of the polyethylene glycol to the volume of water is (0.1-2 g):100 mL.
[0026] Furthermore, the reaction temperature in step 3) is 60-80°C, and the reaction time is 2-4h.
[0027] Furthermore, in step 3), the drying temperature is 100-115° C., and the drying time is 2-4 hours.
[0028] In the above scheme, the particle size of the nano zero-valent metal loaded coffee grounds biochar is 100-500 mesh, and the specific surface area is 300-800m 2 / g, total pore volume is 0.1~0.5cm 3 / g.
[0029] The present invention also provides a method for preparing low-volatile environmentally friendly softening oil, comprising the following steps:
[0030] FCC oil slurry, reduced line oil and nano zero-valent metal loaded coffee grounds biochar are placed in a blender for blending at a blending temperature of 60 to 90° C. and a blending time of 20 to 60 min to obtain low-volatile environmentally friendly softened oil.
[0031] The present invention also provides an application of low-volatile environmentally friendly softening oil in polymer-modified asphalt waterproofing membrane.
[0032] In the above scheme, the amount of the low-volatile environmentally friendly softening oil added to the polymer-modified asphalt waterproofing membrane is 10 to 40% of the mass of the asphalt.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] First, the softening oil (reduction oil, waste oil, cyclohexane oil, etc.) used in traditional polymer modified asphalt waterproofing membranes has a high saturated content and a low aromatic content, resulting in low joint peeling strength and poor anti-aging performance of the waterproofing membrane. The present invention blends the aromatic-rich FCC oil slurry with the saturated-rich reduction oil to adjust the content of each component in the softening oil, thereby providing high-quality softening oil for polymer modified asphalt waterproofing membranes;
[0035] Secondly, the biochar prepared from coffee grounds has a large specific surface area and porous structure, and has an excellent adsorption effect on organic volatiles released by FCC oil slurry and reduced line oil. At the same time, coffee grounds are rich in a large number of natural antioxidants - polyphenols (tannic acid, catechins and flavonoids, etc.) and organic acids (cinnamic acid and vanillic acid, etc.), which can significantly improve the anti-aging performance of polymer-modified asphalt waterproofing membranes;
[0036] Thirdly, the present invention uses polyphenolic hydroxyl compounds such as tannic acid and catechin in coffee grounds extract to reduce FeSO4·7H2O, CuSO4·6H2O or ZnSO4·7H2O to prepare nano zero-valent metals. Nano zero-valent metals have a unique "shell-core" structure, with a thin layer of metal oxide on the surface and a dense zero-valent metal core inside. They have a large specific surface area and reaction activity, and can adsorb and degrade small molecular flue gas volatilized from FCC oil slurry and reduced line oil. Nano zero-valent metals in softening oil can also terminate free radicals formed during asphalt aging through redox reactions, thereby improving the anti-aging properties of waterproof rolls. However, nano zero-valent metals are prone to agglomeration. The present invention loads nano zero-valent metals on coffee grounds biochar, achieving uniform dispersion of nano zero-valent metals on coffee grounds charcoal, which not only solves the problem of easy agglomeration of nano zero-valent metals, but also enhances their dispersibility and stability, while improving the adsorption efficiency and adsorption capacity of coffee grounds charcoal on FCC oil slurry flue gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a scanning electron microscope (SEM) image of the coffee grounds biochar prepared in step 2) of Example 1.
[0038] Figure 2 This is a scanning electron microscope image of pure nano-zero-valent iron.
[0039] Figure 3 This is a scanning electron microscope image of the nano-zero-valent iron-loaded coffee grounds biochar prepared in Example 1. DETAILED DESCRIPTION
[0040] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0041] The raw materials used in the following examples of the present invention are all commercially available, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0042] Example 1
[0043] A low-volatile environmentally friendly softening oil comprises the following raw materials by weight: 100 parts of FCC oil slurry, 120 parts of reduced oil, and 3 parts of nano zero-valent iron loaded coffee grounds biochar. The FCC oil slurry, reduced oil, and nano zero-valent metal loaded coffee grounds biochar are placed in a blender for blending at a blending temperature of 90°C and a blending time of 20 minutes to obtain a low-volatile environmentally friendly softening oil. Among them:
[0044] The freezing point of FCC slurry is 18°C and the density is 1.037 g / cm 3 , the saturated content is 28.12%, and the aromatic content is 54.59%;
[0045] The reduced line oil is a reduced line oil with a solidification point of -8°C and a density of 0.842g / cm 3 , the saturated content is 56.82%, and the aromatic content is 33.58%;
[0046] Nano-zero-valent iron loaded coffee grounds biochar was prepared by the following method:
[0047] 1) 10 g of 200-mesh dry coffee grounds were wrapped in filter paper, placed in a Soxhlet extractor, 200 mL of 70% ethanol solution was prepared as an extractant, and the coffee grounds were subjected to Soxhlet extraction at an extraction temperature of 95° C. for 4 h to obtain an extract and extraction residues;
[0048] 2) placing all the extraction residues obtained in step 1) in a vacuum drying oven at 80° C. for 12 h to fully dry them, and then placing them in a tubular furnace for carbonization under sealed oxygen-free conditions at a heating rate of 10° C. / min, a carbonization temperature of 500° C., and a carbonization time of 4 h to obtain coffee residue biochar with a particle size of 200 mesh;
[0049] 3) After dissolving 0.05 mol FeSO4·7H2O in 100 mL deionized water, the pH was adjusted to 5.5 with a 0.1 mol / L sodium hydroxide solution, and then ultrasonically treated for 15 min. Then, all the coffee grounds biochar obtained in step 2) and all the extracts obtained in step 1) were added and mixed evenly. Then, 1 g of polyethylene glycol (4000) was added, and the temperature was raised to 70°C and stirred for reaction for 4 h. After the reaction was completed, the solid and liquid were separated, and the solid was dried in an oven at 100°C for 4 h to obtain nano zero-valent iron-loaded coffee grounds biochar with a particle size of 200 mesh.
[0050] Figure 1 This is a scanning electron microscope image of the coffee grounds biochar prepared in Example 1. It can be seen that it has a porous structure and a smooth surface without any load. Figure 2 This is a scanning electron microscope image of pure nano-zero-valent iron. It can be seen that it exhibits the characteristic of easy agglomeration. Figure 3 This is a scanning electron microscope image of the nano-zero-valent iron loaded coffee grounds biochar prepared in Example 1. It can be seen that there is evenly dispersed nano-zero-valent iron on the surface of the coffee grounds biochar.
[0051] The specific surface area of the nano-zero-valent iron loaded coffee grounds biochar is 742 m 2 / g, and the total pore volume is 0.388 cm 3 / g, retaining the porous structure of biochar with a large specific surface area and reaction activity, and successfully loading nano-zero-valent iron on coffee grounds biochar, solving the problem of easy agglomeration of nano-zero-valent metals.
[0052] Comparative Example 1-1
[0053] The only difference between Comparative Example 1-1 and Example 1 is that no nano zero-valent iron-loaded coffee grounds biochar is added to the low-volatile environmentally friendly softening oil.
[0054] Comparative Example 1-2
[0055] The only difference between Comparative Example 1-2 and Example 1 is that in the low-volatile environmentally friendly softening oil, the nano zero-valent iron loaded coffee grounds biochar is replaced with an equal mass of coffee grounds biochar prepared in step 2).
[0056] The physical properties and the concentration of harmful substances in the volatiles of the low-volatile environmentally friendly softening oils prepared in Example 1 and Comparative Examples 1-1 and 1-2 were tested.
[0057] (1) Physical property test: The solidification point, 60°C viscosity and 163°C evaporation loss of the softened oil were tested in accordance with GB / T 510-2018 Determination of the solidification point of petroleum products, JTG E20-T0625-2011 Asphalt rotational viscosity test (Brookfield viscometer method) and GB / T11964-2008 Determination of the evaporation loss of petroleum asphalt. The test results are shown in Table 1.
[0058] (2) Test of the concentration of harmful substances in volatiles: The VOCs and H2S contents in the volatiles of softened oil were tested. The test method was as follows: 100 g of softened oil was weighed and poured into a three-necked flask. The three-necked flask was placed in an oil bath, the temperature was set to 180 °C, the opening of the flask was sealed, the speed was set to 300 rpm, and the stirring was stopped after 1 hour. A Korno GT-1000 gas detector was used and set to dual-channel detection mode to detect the contents of VOCs and H2S respectively. The test range was VOCs: 0-2000 ppm, H2S: 0-200 ppm, and the resolution was 0.1 ppm. The test results are shown in Table 1.
[0059] Table 1 Performance and volatile matter concentration of softened oil prepared in Example 1, Comparative Example 1-1 and Comparative Example 1-2
[0060] performance Example 1 Comparative Example 1-1 Comparative Example 1-2 Pour point(℃) -2 -2 -2 60℃ viscosity (mPa·s) 45 40 48 Evaporation loss (%) 0.45 0.58 0.48 VOCs(ppm) 436 1947 968 <![CDATA[H2S(ppm)]]> 2.8 182 55.7
[0061] Application Example 1
[0062] The low-volatile environmentally friendly softening oil prepared by the present invention is applied to polymer-modified asphalt waterproofing membrane. Herein, a polymer-modified asphalt waterproofing membrane is listed, and its components and weight proportions are: 100 parts of asphalt, 10-40 parts of low-volatile environmentally friendly softening oil, 4-12 parts of SBS elastomer, 30-40 parts of rubber powder, and 40-70 parts of filler.
[0063] The low-volatile environmentally friendly softening oil prepared in Example 1 and Comparative Example 1-1 and Comparative Example 1-2 were respectively applied to polymer modified asphalt waterproofing membranes. The specific composition and mass fraction of the polymer modified asphalt waterproofing membranes during application were: 100 parts of asphalt (softening point 49.3°C, 25°C needle penetration 71dmm), 30 parts of low-volatile environmentally friendly softening oil, 8 parts of SBS elastomer, 40 parts of rubber powder, and 60 parts of filler. The specific preparation process is as follows:
[0064] a) Weigh the measured amounts of asphalt and low-volatile environmentally friendly softening oil and put them into the modification tank, control the temperature at 140±5℃, set the speed at 300rpm and stir for 10min;
[0065] b) Add measured portions of SBS elastomer to a, adjust the temperature to 180±5°C, set the speed to 4000 rpm and high-speed shear for 60 minutes;
[0066] c) Add the measured amount of rubber powder to part b, adjust the temperature to 180±5°C, set the speed to 4000rpm and high-speed shear for 90 minutes;
[0067] d) Add a measured amount of filler to c, adjust the temperature to 190±5°C, set the speed to 3000 rpm and high-speed shear for 90 minutes;
[0068] e) Apply d to both sides of the polyester base, control the single-side thickness to 1.5 mm, and cover the upper and lower surfaces with polyethylene isolation films to obtain a polymer-modified asphalt waterproof membrane.
[0069] The physical properties and aging resistance of the polymer modified asphalt waterproof membrane after application of the low-volatile environmentally friendly softening oil prepared in Example 1 and Comparative Example 1-1 and Comparative Example 1-2 were tested.
[0070] (1) Physical property test: The high and low temperature performance of polymer modified asphalt waterproof membrane was tested according to the "Bitumen softening point determination method - Ring and ball method" (GB / T 4507-2014) and "Test methods for building waterproof membrane: Part 14 - Low temperature flexibility of asphalt waterproof membrane" (GB / T 328.14-2007); the joint peel strength was tested according to the "Test methods for building waterproof membrane: Part 20 - Joint peel strength of asphalt waterproof membrane" (GB / T328.20-2007). The test results are shown in Table 2.
[0071] (2) Aging resistance test: The polymer modified asphalt waterproofing membrane was placed in an oven at 80°C for 10 days, and the softening point, low temperature flexibility and joint peeling strength of the waterproofing membrane coating were tested before and after aging. The softening point increment, flexibility change and joint peeling strength retention rate were calculated according to formula (1), formula (2) and formula (3). The test results are shown in Table 2. The smaller the softening point increment and flexibility change before and after aging, the higher the peeling strength retention rate, and the better the aging resistance of the waterproofing membrane.
[0072] Softening point increment = softening point after aging - softening point before aging (1)
[0073] Flexibility change = low temperature flexibility after aging - low temperature flexibility before aging (2)
[0074] Peel strength retention rate = peel strength after aging / peel strength before aging × 100% (3)
[0075] Table 2 Performance of polymer modified asphalt waterproof membranes prepared in Example 1, Comparative Example 1-1 and Comparative Example 1-2
[0076]
[0077] It can be seen from Table 1 and Table 2 that the evaporation loss, VOCs concentration and H2S concentration of the softened oil prepared in Comparative Example 1-2 are much lower than those in Comparative Example 1-1. This is because the adsorption of coffee grounds biochar significantly reduces the volatilization of VOCs and H2S after the softened oil is heated. The polymer modified asphalt waterproofing membrane prepared therefrom has a higher softening point and joint peeling strength and lower low-temperature flexibility. After thermal aging, it has a lower softening point increment and low-temperature flexibility change and a higher joint peeling strength retention rate. This shows that the addition of coffee grounds biochar makes the polymer modified asphalt have better high and low temperature performance and aging resistance. Compared with Comparative Examples 1-2, the evaporation loss, VOCs concentration and H2S concentration of the softened oil prepared in Example 1 are lower, which indicates that the nano zero-valent metal loaded coffee grounds biochar more significantly reduces the volatilization of VOCs and H2S after the softened oil is heated, and the polymer modified asphalt waterproofing membrane prepared therefrom has a higher softening point and joint peel strength, and a lower low-temperature flexibility, a smaller softening point increment and low-temperature flexibility change after thermal aging, and a higher joint peel strength retention rate, which indicates that the addition of nano zero-valent metal loaded coffee grounds biochar can make the polymer modified asphalt have more superior physical properties and anti-aging properties.
[0078] Example 2
[0079] A low-volatile environmentally friendly softening oil comprises the following raw materials by weight: 100 parts of FCC oil slurry, 100 parts of line-cutting oil, and 4 parts of nano-zero-valent copper-loaded coffee grounds biochar. The FCC oil slurry, line-cutting oil, and nano-zero-valent metal-loaded coffee grounds biochar are placed in a blender for blending at a blending temperature of 80° C. for a blending time of 30 minutes to obtain a low-volatile environmentally friendly softening oil. Among them:
[0080] The freezing point of FCC slurry is 20℃ and the density is 1.041g / cm 3 , the saturated content is 22.57%, and the aromatic content is 62.32%;
[0081] The reduced line oil is a reduced second line oil, with a freezing point of -13°C and a density of 0.911 g / cm 3 , the saturated content is 61.25%, and the aromatic content is 25.17%;
[0082] Nano-zero-valent copper loaded coffee grounds biochar was prepared by the following method:
[0083] 1) 5 g of 300-mesh dry coffee grounds were wrapped in filter paper, placed in a Soxhlet extractor, 200 mL of 60% ethanol solution was prepared as an extractant, and the coffee grounds were subjected to Soxhlet extraction at an extraction temperature of 105° C. for 2 h to obtain an extract and extraction residues;
[0084] 2) placing all the extraction residues obtained in step 1) in a vacuum drying oven at 90° C. for 8 h to fully dry them, and then placing them in a tubular furnace for carbonization under sealed oxygen-free conditions at a heating rate of 15° C. / min, a carbonization temperature of 550° C., and a carbonization time of 3 h to obtain coffee residue biochar with a particle size of 300 meshes;
[0085] 3) After dissolving 0.03 mol CuSO4·6H2O in 100 mL of deionized water, the pH was adjusted to 5.5 with a sodium hydroxide solution having a concentration of 0.15 mol / L, and then ultrasonically treated for 5 min. Then, all the coffee grounds biochar obtained in step 2) and all the extracts obtained in step 1) were added and mixed evenly. Then, 1.5 g of polyethylene glycol (4000) was added, and the temperature was raised to 80°C and stirred for reaction for 2 h. After the reaction was completed, the solid and liquid were separated, and the solid was dried in an oven at 105°C for 2.5 h to obtain nano zero-valent copper-loaded coffee grounds biochar with a particle size of 300 mesh.
[0086] The specific surface area of the nano-zero-valent copper-loaded coffee grounds biochar was 519 m 2 / g, and the total pore volume is 0.344 cm 3 / g.
[0087] Comparative Example 2-1
[0088] The only difference between Comparative Example 2-1 and Example 2 is that no nano zero-valent copper loaded coffee grounds biochar is added to the low-volatile environmentally friendly softening oil.
[0089] Comparative Example 2-2
[0090] The only difference between Comparative Example 2-2 and Example 2 is that in the low-volatile environmentally friendly softening oil, the nano zero-valent copper loaded coffee grounds biochar is replaced with an equal mass of coffee grounds biochar prepared in step 2).
[0091] The physical properties and the concentration of harmful substances in the volatiles of the low-volatile environmentally friendly softening oils prepared in Example 1 and Comparative Examples 1-1 and 1-2 were tested. The test results are shown in Table 3.
[0092] Table 3 Performance and volatile matter concentration of softened oil prepared in Example 2, Comparative Example 2-1 and Comparative Example 2-2
[0093] performance Example 2 Comparative Example 2-1 Comparative Example 2-2 Pour point(℃) -6 -6 -6 60℃ viscosity (mPa·s) 35 30 38 Evaporation loss (%) 0.50 0.61 0.55 VOCs(ppm) 372 1742 750 <![CDATA[H2S(ppm)]]> 1.6 192 43.6
[0094] Application Example 2
[0095] The low-volatile environmentally friendly softening oil prepared in Example 2, Comparative Example 2-1 and Comparative Example 2-2 were respectively applied to polymer-modified asphalt waterproof membranes. The specific composition and mass proportion of the polymer-modified asphalt waterproof membranes during application were: 100 parts of asphalt (softening point 48.3°C, 25°C needle penetration 73dmm), 20 parts of low-volatile environmentally friendly softening oil, 6 parts of SBS elastomer, 45 parts of rubber powder, and 57 parts of filler.
[0096] The physical properties and aging resistance of the polymer modified asphalt waterproofing membrane after the low-volatile environmentally friendly softening oil prepared in Example 2 and Comparative Example 2-1 and Comparative Example 2-2 was applied were tested. The test results are shown in Table 4.
[0097] Table 4 Performance of polymer modified asphalt waterproof membranes prepared in Example 2, Comparative Example 2-1 and Comparative Example 2-2
[0098]
[0099] It can be seen from Tables 3 and 4 that, compared with Comparative Examples 2-1 and 2-2, the evaporation loss, VOCs concentration and H2S concentration of the softened oil prepared in Example 2 are the lowest, and the softening point and joint peel strength of the polymer modified asphalt waterproofing membrane prepared therefrom are the highest and the low-temperature flexibility is the lowest. The softening point increment and low-temperature flexibility change after thermal aging are the smallest, and the joint peel strength retention rate is the highest. This indicates that the addition of nano zero-valent metal-loaded coffee grounds biochar significantly reduces the VOCs and H2S concentrations in the volatiles after the softening oil is heated, and effectively improves the physical properties and anti-aging properties of the polymer modified asphalt.
[0100] Example 3
[0101] A low-volatile environmentally friendly softening oil comprises the following raw materials by weight: 100 parts of FCC oil slurry, 80 parts of line-cutting oil, and 2 parts of nano-zero-valent zinc-loaded coffee grounds biochar. The FCC oil slurry, line-cutting oil, and nano-zero-valent metal-loaded coffee grounds biochar are placed in a blender for blending at a blending temperature of 70° C. for a blending time of 40 minutes to obtain a low-volatile environmentally friendly softening oil. Among them:
[0102] The freezing point of FCC slurry is 17℃ and the density is 1.055g / cm 3 , the saturated content is 23.54%, and the aromatic content is 58.14%;
[0103] The reduced line oil is a reduced second line oil, with a freezing point of -20°C and a density of 0.842g / cm 3 , the saturated content is 56.82%, and the aromatic content is 33.58%;
[0104] Nano-Zerovalent Zinc-loaded coffee grounds biochar was prepared by the following method:
[0105] 1) 8 g of 400-mesh dry coffee grounds were wrapped in filter paper, placed in a Soxhlet extractor, 200 mL of 50% ethanol solution was prepared as an extractant, and the coffee grounds were subjected to Soxhlet extraction at an extraction temperature of 100° C. for 3 h to obtain an extract and extraction residues;
[0106] 2) placing all the extraction residues obtained in step 1) in a vacuum drying oven at 85° C. for 8 h to fully dry them, and then placing them in a tubular furnace for carbonization under sealed oxygen-free conditions at a heating rate of 15° C. / min, a carbonization temperature of 600° C., and a carbonization time of 2 h to obtain coffee residue biochar with a particle size of 400 mesh;
[0107] 3) After dissolving 0.03 mol ZnSO4·7H2O in 100 mL deionized water, the pH was adjusted to 6 with a sodium hydroxide solution having a concentration of 0.2 mol / L, and then ultrasonically treated for 10 min. Then, all the coffee grounds biochar obtained in step 2) and all the extracts obtained in step 1) were added and mixed evenly. After adding 0.5 g polyethylene glycol (4000), the temperature was raised to 60°C and stirred for reaction for 4 h. After the reaction was completed, the solid and liquid were separated, and the solid was dried in an oven at 115°C for 2 h to obtain nano zero-valent zinc-loaded coffee grounds biochar with a particle size of 400 mesh.
[0108] The specific surface area of the coffee grounds biochar loaded with nano-zero-valent zinc was 764 m 2 / g, and the total pore volume is 0.488 cm 3 / g.
[0109] Comparative Example 3
[0110] The only difference between Comparative Example 3 and Example 3 is that no nano zero-valent iron-loaded coffee grounds biochar is added to the low-volatile environmentally friendly softening oil.
[0111] The physical properties and the concentration of harmful substances in the volatiles of the low-volatile environmentally friendly softening oils prepared in Example 3 and Comparative Example 3 were tested. The test results are shown in Table 5.
[0112] Table 5 Performance and volatile matter concentration of softened oil prepared in Example 3 and Comparative Example 3
[0113]
[0114]
[0115] Application Example 3
[0116] The low-volatile environmentally friendly softening oil prepared in Example 3 and Comparative Example 3 was respectively applied to polymer-modified asphalt waterproofing membranes. The specific composition and mass proportion of the polymer-modified asphalt waterproofing membranes during application were: 100 parts of asphalt (softening point 49.5°C, 25°C needle penetration 86 dmm), 25 parts of low-volatile environmentally friendly softening oil, 12 parts of SBS elastomer, 40 parts of rubber powder, and 60 parts of filler.
[0117] The physical properties and aging resistance of the polymer modified asphalt waterproofing membrane after the low-volatile environmentally friendly softening oil prepared in Example 3 and Comparative Example 3 was applied were tested. The test results are shown in Table 6.
[0118] Table 6 Performance of polymer modified asphalt waterproof membranes prepared in Example 3 and Comparative Example 3
[0119]
[0120] It can be seen from Tables 5 and 6 that compared with Comparative Example 3, the VOCs and H2S values of the softening oil prepared in Example 3 are significantly reduced, and the softening point, joint peel strength and low-temperature flexibility of the polymer modified asphalt waterproof membrane prepared therefrom are higher than those of Comparative Example 3. The softening point increment and low-temperature flexibility change after thermal aging are lower than those of Comparative Example 3, while the joint peel strength retention rate is higher than that of Comparative Example 3, indicating that nano zero-valent metal-loaded coffee grounds biochar effectively reduces the volatile organic matter generated by heating the softening oil, and the prepared polymer modified asphalt waterproof membrane has better physical properties and anti-aging properties.
[0121] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A low-volatile environmentally friendly softening oil, characterized in that: The method comprises the following raw materials in parts by weight: 100 parts of FCC oil slurry, 50-150 parts of reduced line oil, and 1-5 parts of nano zero-valent metal loaded coffee grounds biochar.
2. The low-volatile environmentally friendly softening oil according to claim 1, characterized in that: The method for preparing nano zero-valent metal loaded coffee grounds biochar comprises the following steps: 1) using an ethanol solution as an extractant to perform Soxhlet extraction on coffee grounds to obtain an extract and extraction grounds; 2) After drying the extraction residue, heating and carbonizing it in a sealed and oxygen-free environment to obtain coffee residue biochar; 3) After the metal salt is dissolved in water, the pH is adjusted with a sodium hydroxide solution, and then the coffee grounds biochar and the extract are added and mixed evenly, and then polyethylene glycol is added, and the temperature is raised and stirred for reaction. After the reaction is completed, the solid and liquid are separated, and the solid is dried to obtain nano zero-valent metal-loaded coffee grounds biochar.
3. The low-volatile environmentally friendly softening oil according to claim 2, characterized in that: The volume fraction of the ethanol solution is 60-80%; the volume ratio of the mass of the coffee grounds to the ethanol solution is (5-10) g:200 mL; the extraction temperature of the Soxhlet extraction is 95-105° C., and the extraction time is 2-4 hours.
4. The low-volatile environmentally friendly softening oil according to claim 2, characterized in that: The extraction residue is vacuum dried at a drying temperature of 70-90°C for 6-12 hours; the carbonization heating rate is 10-15°C / min, the carbonization temperature is 400-600°C, and the carbonization time is 2-4 hours.
5. The low-volatile environmentally friendly softening oil according to claim 2, characterized in that: The metal salt is one of iron salt, copper salt and zinc salt; the mass ratio of the amount of the metal salt to the coffee grounds is (0.02-0.06) mol:10g; the reaction temperature in step 3) is 60-80°C, and the reaction time is 2-4h.
6. The low-volatile environmentally friendly softening oil according to claim 2, characterized in that: The volume ratio of the amount of the metal salt to water is (0.01-0.05) mol:100 mL; the volume ratio of the mass of the polyethylene glycol to water is (0.1-2 g):100 mL; the concentration of the sodium hydroxide solution is 0.1-0.2 mol / L, the pH is adjusted to 5-6, and ultrasonic treatment is performed for 5-15 minutes after adjustment.
7. The low-volatile environmentally friendly softening oil according to claim 1, characterized in that: The nano zero-valent metal loaded coffee grounds biochar has a particle size of 100 to 500 meshes and a specific surface area of 300 to 800 m 2 / g, total pore volume is 0.1~0.5cm 3 / g.
8. The low-volatile environmentally friendly softening oil according to claim 1, characterized in that: The FCC slurry has a freezing point of 15-25°C and a density of 1.03-1.07 g / cm 3 The saturated content is 20-30%, and the aromatic content is 50-65%; the reduced line oil is reduced line oil or reduced line oil, the solidification point is -5--20℃, and the density is 0.8-1.0g / cm 3 The saturated content is 50-65%, and the aromatic content is 20-40%.
9. A method for preparing low-volatile environmentally friendly softened oil according to any one of claims 1 to 8, characterized in that: The following steps are involved: FCC oil slurry, reduced line oil and nano zero-valent metal loaded coffee grounds biochar are placed in a blender for blending at a blending temperature of 60 to 90° C. and a blending time of 20 to 60 min to obtain low-volatile environmentally friendly softened oil.
10. Use of the low-volatile environmentally friendly softening oil according to any one of claims 1 to 8 in polymer-modified asphalt waterproofing membranes.
Citation Information
Patent Citations
Blend oil product and preparation method thereof
CN105400543A
Preparation method and application of nanometer zero-valence bimetal-supported functional charcoal
CN105854797A
Application of nano-iron powder in improvement of ageing resistance of asphalt or reduction of pavement heavy metal ions
CN107033386A
Method for preparing activated carbon by quickly activating waste coffee grounds with solid zinc chloride
CN111943197A
Zero-valent metal-loaded alginate-based carbon sphere, preparation method and application thereof
CN113666460A